2005
DOI: 10.1140/epja/i2004-10281-7
|View full text |Cite
|
Sign up to set email alerts
|

Isospin and symmetry energy effects on nuclear fragment production in liquid-gas-type phase transition region

Abstract: We have demonstrated that the isospin of nuclei influences the fragment production during the nuclear liquid-gas phase transition. Calculations for Au 197 , Sn 124 , La 124 and Kr 78 at various excitation energies were carried out on the basis of the statistical multifragmentation model (SMM). We analyzed the behavior of the critical exponent τ with the excitation energy and its dependence on the critical temperature. Relative yields of fragments were classified with respect to the mass number of the fragments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 32 publications
(60 reference statements)
5
112
0
1
Order By: Relevance
“…The SMM calculation assuming the mass (symmetry energy) evolution during the evaporation therefore leads to larger yields for neutron rich fragments. A similar observation was made by Buyukcizmeci et al [63] in their calculation of the primary and secondary fragment isotopic distributions in 197 Au, 124 Sn and 124 La systems.…”
Section: B Secondary De-excitation Of the Fragmentssupporting
confidence: 84%
See 1 more Smart Citation
“…The SMM calculation assuming the mass (symmetry energy) evolution during the evaporation therefore leads to larger yields for neutron rich fragments. A similar observation was made by Buyukcizmeci et al [63] in their calculation of the primary and secondary fragment isotopic distributions in 197 Au, 124 Sn and 124 La systems.…”
Section: B Secondary De-excitation Of the Fragmentssupporting
confidence: 84%
“…If hot fragments in the freeze-out configuration have smaller γ, their masses at the beginning of the secondary de-excitation will be different, and this effect should be taken into account in the evaporation process. Recently, Buyukcizmeci et al [63] adopted a phenomenological approach to estimate the effect of the symmetry energy evolution during the sequential evaporation. In this approach, they assume liquid drop masses m A,Z = m ld (γ) for the evaporation of the light particles (n, p, d, t, 3 He, α), if the internal excitation energy of the fragment is large (ξ = βE * /A > 1).…”
Section: B Secondary De-excitation Of the Fragmentsmentioning
confidence: 99%
“…Generally, in realistic statistical models most neutrons come from the secondary deexcitation stage, for example, more than 90% in the SMM. If one takes into account a reduction of the symmetry energy of primary fragments, and includes its restoration in the course of deexcitation, the neutron richness of cold final fragments will be larger than predicted by standard codes [65].…”
Section: Deexcitation and Propagation Of Hot Primary Fragmentsmentioning
confidence: 96%
“…The SMM has predicted distinctive features of this phase transition in finite nuclei, such as the plateau-like anomaly in the caloric curve [28,3], which have been later observed in experiments [36,64]. Many other manifestations of the phase transition, such as large fluctuations and bimodality [29,37,65], critical behavior and even values of critical exponents [37,66], have been investigated within this model. The experimental data are usually in agreement with the predictions.…”
Section: Nuclear Liquid-gas Phase Transition Within Statistical Modelsmentioning
confidence: 96%
“…Buyukcizmeci, Ogul and Botvina [31] analyzed SMM simulations for heavy nuclei of various sizes, with excitation energy ranging from 2 to 20 MeV/nucleon. They found that all nuclei exhibit the same caloric curve, depicted in the top panel of fig.…”
Section: Smm: Statistical Multifragmentation Modelmentioning
confidence: 99%